The global proteome of Streptococcus pneumoniae EF3030 under nutrient-defined in vitro conditions - Supradipta De; Larissa M. Busch; Gerhard Burchhardt; Manuela Gesell Salazar; Rabea Schlüter; Leif Steil; Uwe Völker; Sven Hammerschmidt (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionStreptococcus pneumoniae is a human pathobiont that asymptomatically colonizes the upper respiratory tract but can cause severe diseases such as pneumonia, sepsis, and meningitis, as well as non-invasive infections like otitis media and sinusitis. It thrives in the nutrient-limited environment of the nasopharynx and has evolved mechanisms to manage host-induced stress and regulate protein levels accordingly.MethodsTo investigate the molecular biology of S. pneumoniae under in vitro and infection-relevant conditions, a suitable cultivation medium is essential for reproducible experiments. We, therefore optimized a chemically defined minimal medium that mimics the nutrient-limited conditions of the human nasopharynx. This medium was used to cultivate clinical isolates and other streptococcal species for proteomic analysis.ResultThe optimized medium enhanced growth and shortened the lag phase of S. pneumoniae and related species. Using this medium, we analyzed the global proteome of the pneumococcal colonizing strain EF3030 during its transition from early to late logarithmic growth phase. Distinct changes in protein abundance were observed in functional categories such as metabolism, amino acid synthesis, natural competence, RNA and cell wall synthesis, protein degradation, and stress responses. Notably, proteins involved in DNA uptake and processing—such as choline-binding protein CbpD, competence factors ComGA and ComEA, and ssDNA-binding proteins Dpr and DprA—were more abundant in the late log phase.DiscussionThese findings highlight dynamic proteomic changes associated with pneumococcal adaptation to nutrient-limited conditions and provide insights into the biology of strain EF3030 during colonization. The optimized medium offers a reproducible platform for studying pneumococcal physiology and pathogenesis under defined conditions.